2016
DOI: 10.1111/asj.12642
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metritis on the generation of reactive oxygen species by circulating phagocytes and plasma lipopolysaccharide concentration in peripartum dairy cows

Abstract: This study examined the relationship between postpartum metritis, reactive oxygen species (ROS) generation, and plasma lipopolysaccharide (LPS) concentration in peripartum dairy cows. Blood was collected twice weekly from 2 weeks prepartum through 6 weeks postpartum. Whole blood chemiluminescence (WBCL) was measured using the luminol-enhanced zymosan-stimulated chemiluminescence assay. Cows were examined for uterine health disorders and classified into two groups, healthy (n = 11) and metritis (n = 5). Metriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Plasma LPS concentrations are consistently higher in cows with metritis than in healthy cows 0-3 weeks postpartum [27], despite the resolution of symptoms of systemic illness within 1 week postpartum. Usually, circulating LPS is immediately detoxified by hepatocytes in the liver.…”
Section: Lps In Peripheral Bloodmentioning
confidence: 93%
See 1 more Smart Citation
“…Plasma LPS concentrations are consistently higher in cows with metritis than in healthy cows 0-3 weeks postpartum [27], despite the resolution of symptoms of systemic illness within 1 week postpartum. Usually, circulating LPS is immediately detoxified by hepatocytes in the liver.…”
Section: Lps In Peripheral Bloodmentioning
confidence: 93%
“…Plasma LPS concentrations increase in cows with subacute rumen acidosis [24], mastitis [25,26], and uterine inflammation. LPS has been detected in the plasma of cows with metritis [27,28] and endometritis [29], suggesting that it is absorbed from the uterus and transferred to the bloodstream.…”
Section: Lps In Peripheral Bloodmentioning
confidence: 99%
“…Our data indicate that the expression of IL‐1β in PMNs and that of TNFα in PBMC were higher in the RFM cows compared to control cows during postpartum period. These data might suggest that uterine inflammation occurred in RFM cows, as bacterial endotoxin lipopolysaccharide (LPS) is increased in the peripheral blood during uterine inflammation (Magata et al., ) and stimulates the production of IL‐1β and TNFα from neutrophils and macrophages, respectively (Beutler, Hoebe, Du, & Ulevitch, ). In addition, IL‐10 plays an important role in immune cell function; IL‐10 inhibits LPS‐mediated induction of IL‐1β (Fiorentino, Zlotnik, Mosmann, Howard, & O'Garra, ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between uterine health status (UHS), as indicated by VD, and oxidative stress is unclear. Previous studies showed that metritis and VD were associated with increased oxidative stress (Kizil et al, 2010, Magata et al, 2016, but not all (Bicalho et al, 2014). To our knowledge the relationships between inflammatory biomarkers and oxidative stress with uterine health in dairy cows with different dry period lengths is unknown.…”
Section: Introductionmentioning
confidence: 84%
“…In addition, levels of ROM were negatively associated with level of paraoxonase in plasma (r = -0.19, P < 0.01). Cows with acute puerperal metritis had higher oxidative stress, indicated by high malondialdehyde concentrations compared with healthy cows (Kizil et al, 2010, Magata et al, 2016. Increased plasma malondialdehyde concentration which is a thiobarbituric acid reactive species, indicate oxidative status .…”
Section: Discussionmentioning
confidence: 99%